RP-HPLC Method for Simultaneous Estimation of Ceftriaxone and Sulbatam in Parenteral Preparation - DHARUMAN, J.; VASUDEVAN, M.; SOMASEKARAN, K.N.; DHANDAPANI, B.; D. GHODE, PRASHANT (Asian Journal of Chemistry, 2010)
A simple reverse phase liquid chromatographic method has been developed and subsequently validated for simultaneous determination of ceftriaxone and sulbactam in parenteral preparation. The separation was carried out using a mobile phase consisting of phosphate buffer pH 3.5 adjusted with ortho phosphoric acid and acetonitrile (35:65). The column used was Kromasil C8, 5 μ, 15 cm × 4.6 mm id with flow rate of 1 mL/min using PDA detection at 215 nm. The described method was linear over a concentration range of 50-250 and 100-500 μg/mL for the assay of sulbactam and ceftriaxone, respectively. Ibuprofen (50 μg/mL) was used as internal standard. The retention times of sulbactam, ceftriaxone and ibuprofen were found to be 2.3, 4.2 and 5.1 min, respectively. Results of analysis were validated statistically and by recovery studies. The limit of quantification (LOQ) for ceftriaxone and sulbactam were found to be 20 and 10 μg/mL, respectively. The results of the study showed that the proposed RP-HPLC method is simple, rapid, precise and accurate, which is useful for the routine determination of ceftriaxone and sulbactam bulk drug and in its pharmaceutical dosage form.